2016
DOI: 10.5578/tt.26423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of healthcare associated pneumonia in Turkey

Abstract: Clinical characteristics and outcome of healthcare associated pneumonia in Turkey Introduction: Pneumonia in cases with preceding hospitalization, hemodialysis, intravenous therapy, wound care, or chemotherapy within the prior 30 days and residence in nursing homes are defined as healthcare associated pneumonia (HCAP). The aim of this study was to compare the demographic and laboratory data, isolated causative agents and prognosis of patients with communityacquired pneumonia (CAP) and HCAP in a large populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…All studies comparing HCAP and CAP patients confirmed differences with regard to older age and higher comorbidity. Three retrospective studiesdone from Korea [17], one from China [18] and one from Turkey [19]dprovided further general descriptions of HCAP populations. Otherwise, clinical characteristics were similar to those described in the original reports [2e6].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…All studies comparing HCAP and CAP patients confirmed differences with regard to older age and higher comorbidity. Three retrospective studiesdone from Korea [17], one from China [18] and one from Turkey [19]dprovided further general descriptions of HCAP populations. Otherwise, clinical characteristics were similar to those described in the original reports [2e6].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…In immunocompromised patients with CAP, Enterobacteriaceae spp., Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and extended-spectrum beta-lactamase positive are more frequent [75]. The study by Gunduz et al [76] conducted in Turkey between 2009 and 2013 observed that the causative bacteria isolated most fre-quently in patients with CAP are S. pneumoniae, P. aeruginosa,Escherichia coli, Haemophilus influenzae, S. aureus, Klebsiella pneumoniae, Streptococcus spp. and Moraxella catarrhalis.…”
Section: 22mentioning
confidence: 99%
“…In immunocompromised patients with CAP, Enterobacteriaceae spp., Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and extended-spectrum beta-lactamase positive are more frequent (15). The study by Gunduz et al (16) conducted in Turkey between 2009 and 2013 observed that the causative bacteria isolated most frequently in patients with CAP are S. pneumoniae, P. aeruginosa, Escherichia coli, Haemophilus influenzae, S. aureus, Klebsiella pneumoniae, Streptococcus spp. and Moraxella catarrhalis.…”
Section: Causative Microorganismsmentioning
confidence: 99%